2009
DOI: 10.1039/b817540c
|View full text |Cite
|
Sign up to set email alerts
|

Density functional studies on the exchange interaction of a dinuclear Gd(iii)–Cu(ii) complex: method assessment, magnetic coupling mechanism and magneto-structural correlations

Abstract: Density functional calculations have been performed on a [Gd(iii)Cu(ii)] complex [L(1)CuGd(O(2)CCF(3))(3)(C(2)H(5)OH)(2)] () (where L(1) is N,N'-bis(3-ethoxy-salicylidene)-1,2-diamino-2-methylpropanato) with an aim of assessing a suitable functional within the DFT formalism to understand the mechanism of magnetic coupling and also to develop magneto-structural correlations. Encouraging results have been obtained in our studies where the application of B3LYP on the crystal structure of yields a ferromagnetic J … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
125
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(137 citation statements)
references
References 64 publications
12
125
0
Order By: Relevance
“…Since then, a complex of lower symmetry with a phenoxo-hydroxo double bridge confirmed that a ferromagnetic interaction is still present [7]. Density functional studies on the exchange interaction of a dinuclear Cu-Gd complex published very recently suggest that the partially occupied Gd III 5d orbitals have a major role on the magnetic coupling [8]. In the present work, we want to describe new complexes characterized by an original bridging network.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Since then, a complex of lower symmetry with a phenoxo-hydroxo double bridge confirmed that a ferromagnetic interaction is still present [7]. Density functional studies on the exchange interaction of a dinuclear Cu-Gd complex published very recently suggest that the partially occupied Gd III 5d orbitals have a major role on the magnetic coupling [8]. In the present work, we want to describe new complexes characterized by an original bridging network.…”
Section: Introductionmentioning
confidence: 58%
“…In a very recent work dealing with the Cu-Gd exchange interaction, DFT calculations demonstrate that replacement of one bridging oxygen by a hydrogen atom in a double bridge should give antiferromagnetic interactions [8]. In other words, this would mean that an unique bridge, as in the present complexes (LCu) 2 Gd(NO 3 ) 3 ÁH 2 O 5 and LCuGd(hfa) 3 6, should yield antiferromagnetic interactions.…”
Section: Discussionmentioning
confidence: 91%
“…A deeper understanding of the microscopic processes related to magnetic interactions has been a very interesting topic in computational chemistry since the first half of the twentieth century [1][2][3][4][5][6][7][8][9][10]. The idea of using molecules, rather than the ionic and metallic lattices of typical magnets, stems from the rapid development of functional molecular materials, and gives a better insight into the nature of coupling between paramagnetic centers.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a spin polarization mechanism involving the Cu 3d orbital but with the empty Gd 6s one was proposed by Gatteschi et al [17,18]. According to Rajaraman et al [19] and Singh et al [20] the 5d orbitals should be considered to explain the interaction mechanism, since they are important for the exchange interaction through spin delocalization from both the 4f orbitals of the Gd(III) ion and the 3d orbitals of the transition metal ions. Recently, Ruiz et al [21] based on the analysis of the atomic and orbital spin populations revealed that the presence of spin density in the Gd 5d orbital is mainly due to the spin polarization of the Gd-ligand bonding electron pairs involving the formally empty 5d orbitals, while a delocalization mechanism from the 3d orbitals of the transition metal can be ruled out.…”
mentioning
confidence: 94%
“…All in all, we should state that given the structure of the coupling between Cu1 and Cu3 the obtained value of the constant J CuCu should be taken cautiously and looked upon only as the upper limit for its true value. The mechanism of the Cu-Gd interaction and mainly the role of the "empty" Gd orbitals in the exchange interactions are the subject of many research [11,[16][17][18][19][20][21]. Andruh et al [11,16] suggested the unique electron transfer mechanism from a singly occupied 3d orbital centered on copper toward an empty 5d orbital centered on gadolinium.…”
mentioning
confidence: 99%